Pharmacovigilance for antiretroviral drugs in Africa, lessons from a study in Abidjan, Cote d’Ivoire: Pharmacovigilance for antiretroviral drugs in Africa - Jaquet, Antoine (2011)
BACKGROUND: While antiretroviral treatment (ART)-related adverse drug reactions (ADR) are documented in industrialized countries, there is no pre-existing surveillance system dedicated to ADR monitoring in most African countries. We assessed knowledge towards pharmacovigilance among ART prescribers and available capacity of HIV clinics to conduct ADR monitoring in Abidjan, Côte d’Ivoire. METHODS: A questionnaire was administered to ART prescribers, to assess their knowledge towards the occurrence of ADRs. A retrospective ADR survey was also conducted, based on a data query of treatment modification/interruptions in three HIV clinics. Clinical monitors went back to medical charts to review and validate the reasons of the treatment modification/interruptions. RESULTS: Of the 81 ART prescribers interviewed, 25 (31%) declared not grading ADRs and 12 (14.8%) declared notifying ADRs to the national regulatory authorities. Among 5,252 adult ART-treated patients who attended the participating clinics in 2008, 599 treatment modifications were identified. Reasons for treatment modification/interruptions identified in the electronic database were documented in the medical charts in 554 (92.5%) cases, ADR accounting for 273 (45.5%) cases. Toxicity related to ART was graded in only 58 (21%) cases in the medical charts. DISCUSSION: This study describes challenges limiting the implementation of reliable pharmacovigilance activities in HIV clinics in Côte d’Ivoire. The lack of knowledge of ART prescribers concerning ADR grading does not support the spontaneous reporting of ADRs. Using treatment modification/interruptions for ADR monitoring appears feasible but improvements are needed to respond to key questions related to drug toxicities in the context of ART scale up in Africa.